Mediation Effects of Firm Leverage in Malaysia: Partial Least Squares –Structural Equation Modelling (PLS-SEM) - Nur Ainna Ramli; Gilbert Nartea (International Journal of Economics and Financial Issues, 2016)
In theory, capital structure determinant is a cause-effect model. We investigate the simultaneously of cause-effect framework on the impact of specific attributes on firm's financial performance through leverage which acts as a mediation variable. We use the PLS-SEM that capable of providing a greater understanding of the prediction for the construct relationship among each other with simultaneous techniques with only one time process (Chin, 1998). We endeavour to examine in a complex model that consists with 14 construct (LVs) and 33 indicators in Malaysia for the period from 1990 to 2010. The implication is that the Malaysian firms could attempt to choose less risky route, as Malaysia is recognised as a “market-based oriented”. In addition, we find that some attributes could influence the relationship to firm's financial performance by indirect effect (leverage). Thus, firms tend to act with partial action on their capital structure, which believe to attain a sustainable performance. Keywords: Capital structure, Partial Least Squares, Structural Equation Modelling, mediation effects